2018
DOI: 10.1093/nar/gky1093
|View full text |Cite
|
Sign up to set email alerts
|

The neurodegenerative diseases ALS and SMA are linked at the molecular level via the ASC-1 complex

Abstract: Understanding the molecular pathways disrupted in motor neuron diseases is urgently needed. Here, we employed CRISPR knockout (KO) to investigate the functions of four ALS-causative RNA/DNA binding proteins (FUS, EWSR1, TAF15 and MATR3) within the RNAP II/U1 snRNP machinery. We found that each of these structurally related proteins has distinct roles with FUS KO resulting in loss of U1 snRNP and the SMN complex, EWSR1 KO causing dissociation of the tRNA ligase complex, and TAF15 KO resulting in loss of transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 92 publications
0
41
0
Order By: Relevance
“…Finally, it will be important to understand the functional consequences of U1-mediated mRNA 3ʹ processing inhibition. For example, the expression and distribution of U1 snRNP have been demonstrated to be altered in Alzheimer Disease and other Neurodegenerative Disease [64][65][66], whether U1-mediated 3ʹ processing regulation directly contributes to these diseases remains elusive. A great challenge for this study is the dual role of U1 snRNP in splicing and PAS suppression, which makes data difficult to interpret.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it will be important to understand the functional consequences of U1-mediated mRNA 3ʹ processing inhibition. For example, the expression and distribution of U1 snRNP have been demonstrated to be altered in Alzheimer Disease and other Neurodegenerative Disease [64][65][66], whether U1-mediated 3ʹ processing regulation directly contributes to these diseases remains elusive. A great challenge for this study is the dual role of U1 snRNP in splicing and PAS suppression, which makes data difficult to interpret.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, EWS appears to be mislocalized in the cytoplasm of motor neurons in sporadic ALS in the absence of EWS mutations [19,124] and FUS-FTD [81]. Like for FUS and TDP43, EWS interacts with SMN and is required for its function in splicing, suggesting a role of EWS in SMA [125,126].…”
Section: Ewsmentioning
confidence: 99%
“…Moreover, ASC-1 contains a conserved C-terminal ASCH domain with putative RNA-binding activity predicted in silico to coordinate pre-mRNA processing 21,22 . Interestingly, the ASC-1 complex has been recently implicated in Amyotrophic Lateral Sclerosis (ALS) pathogenesis, being proposed as a common link between ALS and SMA 23 . We demonstrated that ASC-1 plays a pivotal role in muscle, its absence leading to defects in human myotube growth 14 .…”
Section: Introductionmentioning
confidence: 99%